Direct and Spillover Effects of Unconventional Monetary and Exchange Rate Policies - Gagnon, Joseph (IMF Working Papers; Working Paper, 2017)
This paper explores the effects of unconventional monetary and exchange rate policies. We find that official foreign asset purchases have large effects on current accounts that diminish as capital mobility rises and spill over to financially integrated countries. There is an additional effect through the stock of central bank assets. Domestic asset purchases have an effect on current accounts only when capital mobility is low. We also find that rising US bond yields drive foreign yields, stock prices and depreciations, but less so on days of policy announcements. We develop a theoretical model that is broadly consistent with our results.